Are women who work in bars, guesthouses and similar facilities a suitable study population for vaginal microbicide trials in Africa? - Andrew Vallely; Ian R Hambleton; Stella Kasindi; Louise Knight; Suzanna C Francis; Tobias Chirwa; Dean Everett; Charles Shagi; Claire Cook; Celia Barberousse; Deborah Watson-Jones; John Changalucha; et al. (PLoS ONE)
Background A feasibility study was conducted to investigate whether an occupational at-risk cohort of women in Mwanza, Tanzania are a suitable study population for future phase III vaginal microbicide trials. Methodology/principal findings 1573 women aged 16-54 y working in traditional and modern bars, restaurants, hotels, guesthouses or as local food-handlers were enrolled at community-based reproductive health clinics, provided specimens for HIV/STI and pregnancy testing, and asked to attend three-monthly clinical follow-up visits for 12-months. HIV positive and negative women were eligible to enter the feasibility study and to receive free reproductive health services at any time. HIV prevalence at baseline was 26.5% (417/1573). HIV incidence among 1156 sero-negative women attending at baseline was 2.9/100PYs. Among 1020 HIV sero-negative, non-pregnant women, HIV incidence was 2.0/100PYs, HSV-2 incidence 12.7/100PYs and pregnancy rate 17.8/100PYs. Retention at three-months was 76.3% (778/1020). Among 771 HIV sero-negative, non-pregnant women attending at three-months, subsequent follow-up at 6, 9 and 12-months was 83.7%, 79.6%, and 72.1% respectively. Older women, those who had not moved home or changed their place of work in the last year, and women working in traditional bars or as local food handlers had the highest re-attendance. Conclusions/significance Women working in food outlets and recreational facilities in Tanzania and other parts of Africa may be a suitable study population for microbicide and other HIV prevention trials. Effective locally-appropriate strategies to address high pregnancy rates and early losses to follow-up are essential to minimise risk to clinical trials in these settings.